Distinct and Cooperative Functions for the Protocadherin-α, -β and -γ Clusters in Neuronal Survival and Axon Targeting - Hasegawa, Sonoko; Kumagai, Makiko; Hagihara, Mitsue; Nishimaru, Hiroshi; Hirano, Keizo; Kaneko, Ryosuke; Okayama, Atsushi; Hirayama, Teruyoshi; Sanbo, Makoto; Hirabayashi, Masumi; Watanabe, Masahiko; Hirabayashi, Takahiro; et al. (Frontiers in Molecular Neuroscience, 2016)
The clustered protocadherin (Pcdh) genes are divided into the Pcdhα, Pcdhβ, and Pcdhγ clusters. Gene-disruption analyses in mice have revealed the in vivo functions of the Pcdhα and Pcdhγ clusters. However, all Pcdh protein isoforms form combinatorial cis-hetero dimers and enter trans-homophilic interactions. Here we addressed distinct and cooperative functions in the Pcdh clusters by generating six cluster-deletion mutants (Δα, Δβ, Δγ, Δαβ, Δβγ, and Δαβγ) and comparing their phenotypes: Δα, Δβ, and Δαβ mutants were viable and fertile; Δγ mutants lived less than 12 hours; and Δβγ and Δαβγ mutants died shortly after birth. The Pcdhα, Pcdhβ, and Pcdhγ clusters were individually and cooperatively important in olfactory-axon targeting and spinal-cord neuron survival. Neurodegeneration was most severe in Δαβγ mutants, indicating that Pcdhα and Pcdhβ function cooperatively for neuronal survival. The Pcdhα, Pcdhβ, and Pcdhγ clusters share roles in olfactory-axon targeting and neuronal survival, although to different degrees.